ARTERIOVENOUS ACCESS IN CHILDREN: Arteriovenous Access in Children - Imtiaz, Nauman (Pakistan Armed Forces Medical Journal, 2016)
Objective: To evaluate arteriovenous access (AVA) in children for patency and to compare our results with other studies. Study Design: Cross sectional descriptive study. Place and Duration of Study: Combined Military Hospital Rawalpindi and Combined Military Hospital Lahore, from 1st August 2005 to 15th June 2011. Patients and Methods: Total 35 AVA patients were included in the study. Record was made of age, weight, gender, physical examination of vein, findings of duplex venous mapping, plan of AVA and procedure performed. Twenty nine cases (82.8 %) were already undergoing hemodialysis. Thirty (85.7%) cases were operated under general anesthesia and only 5 (14.2%) under local anesthesia. All end-to-side fistulae were made. Meticulous microsurgical technique was used. Patients were examined on 1st, 2nd and 10th postoperative days, and then every month for at least 12 months. Primary failure, complications and revision procedures were recorded. SPSS version 19.00 was used for statistical analysis. Primary and secondary patencies were calculated. Kaplan – Meier curve was used to express both primary and secondary patency. Results: Out of 35 AVA, 20 (57.1%) radiocephalic (RCAVA), 11(31.4%) brachiocephalic (BCAVA) and 4 (11.4%) brachiobasilic (BBAVA) were made. Three (8.5%) AVA thrombosed within 48 hours. Thrombectomy was done in all but only one (2.8%) was saved. Six (17.1%) presented with failure within next 6 months (4 RCAVA and 2 BCAVA).Only 1 (2.8%) RCAVA was saved. One RCAVA, BCAVA and BBAVA each presented with failure between 6 and 12 months. Again 1 RCAVA was saved. Primary failure occurred in 4 (11.4 %) patients. Primary patency rate at 6 months and 12 months was 74.2% and 65.7% respectively while secondary patency rate was 80% and 74.2% at 6 and 12 months respectively. Conclusion: Primary and secondary patency rates of AVA in children in our study were comparable to most of the similar studies.